Effect of sitting posture on pelvic injury risk under vertical loading. (August 2020) - Tse, Kwong Ming; Lee Robinson, Dale; Franklyn, Melanie; Zhang, Jiang Yue; Spratley, E. Meade; Salzar, Robert Scott; Fernandez, Justin; Ackland, David Charles; Lee, Peter Vee Sin
Abstract: Underbody blast (UBB) attacks on military vehicles can result in severe pelvic injuries to the vehicle occupants. The aim of this study was to evaluate the biomechanical responses of the pelvis to UBB-like vertical loading in different seated postures. High-rate axial loading were performed on six defleshed human cadaveric pelves, whilst a three-dimensional finite element model of a human pelvis was created and used to simulate the high-rate loading with the model responses validated against experimental measurements. Three pelvic orientation corresponding to normal, upright, and relaxed seated postures, along with three different sacral slope angles representing the range of relative pelvis and sacrum positions known to exist across the population, were studied. The results showed that a decrease in posterior pelvic tilt slightly reduced the severity of sacral fracture, while an increase in sacral angle extended the region of anterior sacral fracture but reduced the extent to which the dorsal sacrum fractured. Across all seated postures, the predicted fractures of the ischial tuberosity, ischium, pubic rami and sacrum coincided with the typical pelvic fracture patterns observed in UBB events. The present study suggests that adopting an upright initial seated posture prior to an UBB event may reduce the risk of pelvic injuries. Highlights: This study evaluates how sitting posture affects the pelvis injury risk in UBB. No reported work recommends best sitting posture for military vehicle occupants. The model-to-cadaveric experimental approach adopted has no precedent in pelvis. The pelvis model includes detailed commonly-neglected anatomic features.